Development of Rice Husk Ash as Sustainable Sand Dice Considering to Permeability Characteristic - Yusron, Rifky Maulana; Hidayat, Khoirul; Rifai, Emon (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2025)
Through unwavering professionalism and adherence to ethical standards, our engineering team is at the forefront of sustainable development, utilizing advanced technology and innovative sand-casting techniques to create environmentally-friendly solution. Sand-casting offers material flexibility over large part capabilities on low volume production. This method also offers lower casting costs and generates less carbon print. Currently, sand casting use water, bentonite, and quartz sand as dice materials. Researchers are looking for to find quartz sand substitution materials because they are not sustainable and expensive. Rice-husk ass is a waste post-harvesting material, it had silica and magnesium oxide which has characteristics similar to quartz sand. The aim of this research is to observe permeability characteristic of sand dice with rice-husk ass and bentonite percentage additive mixture. This research using full factorial 32 as experimental design. The independent variable on this research is composition of rice husk ass and bentonite. The composition of rice husk ash has 3 levels of 6%, 8% and 10%. bentonite composition also has similar level but different levels of 8%, 9% and 10%. The lowest permeability is 320 ml/min, it achieved on 6% rice husk ash and 8% bentonite at second replication. Meanwhile, the highest value of permeability is 450ml/min, it achieved on 10% rice husk ash and 10% bentonite. The results of data processing using descriptive statistics reveal composition mixture of rice husk ass and bentonite is directly proportional. The higher composition of rice husk ash mixture increasing permeability on sand casting dice. General linear Model ANOVA analyse show that composition rice husk ass and bentonite have significant influence to permeability of sand-casting dice. Result of analyse show rice husk ass has dominant contribution on permeability on sand casting dice. Contribution of rice husk ass is 58,78%, bentonite 22,03% prior to permeability on sand casting dice.